2013
DOI: 10.1074/jbc.m112.419788
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6/Signal Transducer and Activator of Transcription 3 (STAT3) Pathway Is Essential for Macrophage Infiltration and Myoblast Proliferation during Muscle Regeneration

Abstract: Background: Interleukin-6 (IL-6), as a multifunctional cytokine, was involved in the inflammation microenvironment of muscle regeneration. Results: In mice lacking IL-6, less macrophage recruitment and decreased myoblast proliferation impairs muscle regeneration. Conclusion: In monocytes/macrophages, activation of the IL-6/STAT3 pathway is critical to macrophage migration and myoblast proliferation during muscle regeneration. Significance: IL-6/STAT3 pathway is essential for muscle regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
203
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(221 citation statements)
references
References 37 publications
16
203
1
1
Order By: Relevance
“…27 IL-6 knockout mice were shown to have an impaired hypertrophic response to overloading. 28 We previously reported that myogenesis response to muscle injury was blunted in IL-6 knockout mice, 29 which proved the positive effect of IL-6 on myogenesis. Other groups have also reported that electrical stimulation increases IL-6 in both cultured C2C12 cells 30 and human primary muscle cells.…”
Section: Discussionmentioning
confidence: 85%
“…27 IL-6 knockout mice were shown to have an impaired hypertrophic response to overloading. 28 We previously reported that myogenesis response to muscle injury was blunted in IL-6 knockout mice, 29 which proved the positive effect of IL-6 on myogenesis. Other groups have also reported that electrical stimulation increases IL-6 in both cultured C2C12 cells 30 and human primary muscle cells.…”
Section: Discussionmentioning
confidence: 85%
“…The effects of PBM on macrophage phenotypes are beginning to be described in cell cultures studies,10, 30, 31, 32, 33, 34 evidencing that this therapeutic modality, especially using the NIR wavelength, is capable of altering the polarization of these cells in vitro. In vivo experiments have demonstrated that PBM (808 nm) can shift the phenotype of brain microglial polarization from the pro‐inflammatory phenotype (M1) to the anti‐inflammatory (M2) phenotype after ischemic stroke, promoting cortical neurogenesis 35.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that macrophages and stromal cells bidirectionally communicate to support repair in several different tissue microenvironments. For instance, macrophages are necessary for the formation of niches required for limb regeneration in salamanders (74), for skeletal muscle regeneration following toxinmediated injury (75), and for cardiac regeneration in neonatal mice after MI (38). With a growing appreciation for macrophage heterogeneity, it will be important to delineate the factors governing the polarization (denoted by transcriptional regulation and expression of surface markers) of macrophages during ischemic injury (24,25,43).…”
Section: Macrophage Cell Isolation and Differentiationmentioning
confidence: 99%